Fatal pulmonary sporotrichosis caused by Sporothrix brasiliensis in Northeast Brazil. - Manoella do Monte Alves; Eveline Pipolo Milan; Walicyranison Plinio da Silva-Rocha; Alexandre Soares de Sena da Costa; Bruno Araújo Maciel; Pedro Henrique Cavalcante Vale; Paulo Roberto de Albuquerque; Soraia Lopes Lima; Analy Salles de Azevedo Melo; Anderson Messias Rodrigues; Guilherme Maranhão Chaves (Public Library of Science (PLoS), 2020)
BACKGROUND:A relevant case of pulmonary sporotrichosis due to Sporothrix brasiliensis is reported in a 50-year-old immunocompetent woman who had no history of skin trauma, but was in close contact with several stray cats at her nap time. The patient was hospitalized after 7 months of illness. The survey was conducted for pulmonary tuberculosis, an endemic disease in Brazil. She presented multiple central pulmonary nodules images, with central cavitation. METHODOLOGY/PRINCIPAL FINDINGS:The patient bronchoalveolar lavage was cultured and Sporothrix sp. growth was obtained. Then, the isolate (LMMM1097) was accurately identified to the species level by using species-specific polymerase chain reaction (PCR). Molecular diagnosis revealed that the emerging species Sporothrix brasiliensis was the agent of primary pulmonary sporotrichosis and the patient was treated with Amphotericin B lipid complex, but presented severe clinical symptoms and the fatal outcome was observed at day 25 after hospitalization. CONCLUSIONS/SIGNIFICANCE:Our report adds important contributions to the clinical-epidemiological features of sporotrichosis, showing the geographic expansion of the agent within different regions of Brazil and a rare clinical manifestation (primary pulmonary sporotrichosis) caused by the emerging agent S. brasiliensis in an immunocompetent female patient.